Thin layer drying of red pepper - Akpinar, EK; Bicer, Y; Yildiz, C (Elsevier Sci Ltd, 2003)
The thin layer drying behaviour of red pepper slices is experimentally investigated in a convective dryer and the mathematical modelling by using thin layer drying models in literature is performed. Drying experiments were conducted at inlet temperatures of drying air of 55, 60 and 70 degreesC and at a drying air velocity of 1.5 m/s. Eleven different thin layer mathematical drying models were compared according to their coefficient of correlation to estimate drying curves. The effects of drying air temperature on the model constants and coefficients were predicted by regression models. According to the results, an approximation of the diffusion model could satisfactorily describe the drying curve of red peppers with a correlation coefficient (r) of 0.9987. The constants and coefficients of this model could be explained by the effect of drying air temperature. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: drying; thin layer; red pepper; mathematical modelling